Characteristics of post-menopausal women with genitourinary syndrome of menopause: Implications for vulvovaginal atrophy diagnosis and treatment selection. Issue 4 (August 2015) - Castelo-Branco, Camil; Biglia, Nicoletta; Nappi, Rossella E.; Schwenkhagen, Anne; Palacios, Santiago
Highlights The attitudes of menopausal women towards VVA symptoms allow for the definition of different profiles. Women profiles are easily identifiable with varying representation among countries. This study identified eight post-menopausal women's profiles. Pragmatist, vivacious and expressive were the most proactive profiles searching for VVA solutions. Reserved and stoic women required a communication effort to diagnose and treat in routine clinical practice.